A Current International Bibliography of the Literature of the History of Cartography on the WWW: of Whom, by Whom, and for Whom? - Herbert, Francis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
I shall briefly mention, as a discussion basis, various facets of the proposal that have occurred to me under the headings: Currency, Countries, Contributions, Content, Compilation, Control & Co-operation, and Computer compatibility.